2018
DOI: 10.1002/msc.1237
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a fatigue management in work programme on meeting work demands of individuals with rheumatic diseases: A pilot study

Abstract: Significant improvements were reported in participants' ability to meet various demands of their work 3 months post-FAME-W. These findings suggest that FAME-W has the potential to assist individuals with RDs to meet the demands of their work, although further research is required to test the effectiveness of this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Other studies have explored the impact of AS on work and have reported that individuals with AS are three times more likely to resign from work than the general population [45]. Work-focused self-management interventions result in significant improvements in work performance pain, fatigue, and mood [46]. This indicates that work-focused self-management interventions should be offered to individuals who report difficulty in work due to their fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have explored the impact of AS on work and have reported that individuals with AS are three times more likely to resign from work than the general population [45]. Work-focused self-management interventions result in significant improvements in work performance pain, fatigue, and mood [46]. This indicates that work-focused self-management interventions should be offered to individuals who report difficulty in work due to their fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…8,12 An uncontrolled pilot study of a self-management programme specifically for fatigue at work for patients with inflammatory rheumatic diseases examined presenteeism and demonstrated improvements in four domains of functioning while at work: physical and mental demands, work scheduling and work outputs. 112 It is possible that the weekly review of daily activity diaries in the RAFT programme, accompanied by encouragement to break up large periods of intense activity through factoring in short breaks, may help presenteeism.…”
Section: Discussionmentioning
confidence: 99%
“…However, even with high levels of flexibility and autonomy, fatigue remains a persistent challenge to employment for people with RDs (Holland & Collins, ; Mancuso et al, ). Thus, further research on fatigue management interventions is essential (McCormack, O'Shea, Doran, & Connolly, ),…”
Section: Discussionmentioning
confidence: 99%